Next generation intelligent environments ambient adaptive systems - Heinroth, Tobias; Minker, Wolfgang (Springer, 2011)
Intelligent environments represent an emerging topic in research. Next Generation Intelligent Environments: Ambient Adaptive Systems will cover all key topics in the field of intelligent ambient adaptive systems. It focuses on the results worked out within the framework of the ATRACO (Adaptive and TRusted Ambient eCOlogies) project. The theoretical background, the developed prototypes, and the evaluated results form a fertile ground useful for the broad intelligent environments scientific community as well as for industrial interest groups. Features of the book include: A unique and original collection of chapters on intelligent ambient adaptive systems Broad coverage of the field of intelligent environments research and evaluation, as well as topics such as adaptation within activity spheres Developed prototypes as examples for readers Computer scientists, engineers and others who work in the area of ambient environments will find the edition interesting and useful to their own work. In addition, graduate students and Ph.D. students specializing in the area of intelligent environments may also use this book to get a concrete idea of the major issues to consider when developing intelligent environments in practice.